Development of Comics for Slow Learner Children as Assistive Media at MI Modern Sakti Permata Hati Ibu Tulungagung - Saktiani, Sri; Rahman, Diniy Hidayatur (Jurnal ORTOPEDAGOGIA, 2025)
Comics have emerged as a valuable tool in the realm of education, particularly as an assistive medium. This study delves into the development of comics for children with special needs in the context of primary education. Children with special needs often require additional support and tailored conditions to foster their optimal development. This study focuses on analyzing the development of comic products utilized at MI Modern Sakti Permatahati Ibu Tulungagung. The ADDIE model, a research and development theory comprising five steps, served as the methodological framework for this study. The analysis of the findings was conducted using a descriptive narrative approach. The findings of this study reveal that comics, in essence, function as a learning medium that can stimulate students' receptivity to the material or instruction provided by the teacher. This context is particularly relevant to comics as an assistive medium in the realm of habituation. Comics introduce a unique approach to facilitating learning, making the habituation process more manageable. Students can engage with both visual and textual elements, enhancing their comprehension.